Three-Phase Motor Control using Modified Reference Wave - Aghion, C.; Ursaru, O.; Lucanu, M. (Elektronika ir Elektrotechnika, 2010)
This paper describes the implementation of a modified reference wave using discontinuous pulse width modulation DPWM-S2 technique. The number of commutations is reduced as, for two intervals of time (out of six), some transistors are in continuous conduction, and power losses in commutation should be in theory by smaller if SPWM or SVM techniques were used. Ill. 9, bibl. 8 (in English; abstracts in English, Russian and Lithuanian).